(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-83-91 The article deals with specific features of the ethnical view of the world in advertising accounting for regional differences. The definition of the concept of an advertising text with regional differences alongside with the concepts of ethnicity, ethnic identity, ethnic worldview in regional media advertising are analyzed on the linguoculturological approach and are presented in the article. Some domestic and foreign views on the study of identity in general are highlighted; linguistic and nonlinguistic ways of explicating the ethnic view of the world in advertising accounting for regional differences are established. Observations of the ethnic view of the world of the people of the region in question in advertising texts as a special ethno-semiotic space that convey lore about the goods/services of the world through the prism of the culture elements of the ethnic group in terms of signs are made. It is concluded that advertising accounting for regional differences making an appeal to semiotics of the ethnic identity of the consumer provides some additional opportunities to stand against the destructive influence of globalization processes promoting the consolidation and maintaining the unique character of the cultures and the integrity of the peoples of the Russian Federation. Key words: ethnicity, ethnic worldview, ethnic identity, ethnic stereotypes, advertising discourse, advertising text with regionally influenced differences